Apakah Informasi Akuntansi Penting Bagi Pemilik UMKM? - Glenn Andrenossa; Theresia Octaviani; Andreas Fajar Christmas (Balance: Media Informasi Akuntansi dan Keuangan, 2023)
Abstract:The importance of accounting information is influenced by the goals to be achieved by the owner. However, some of the owners also feel that there are obstacles they face when they want to present a financial report. The research design uses a survey method with a descriptive approach and uses a purposive sampling method in taking the sample. The population in this study consisted of 55 SMEs engaged in the Coffee Shop business in Palangka Raya, Central Kalimantan, Indonesia. The results show that not all SMEs carry out accounting records for their business, on the grounds that they do not have an accountant to record their business transactions. In addition, the SMEs owner does not have knowledge of accounting records. In addition, they also think that accounting records are not too important to do in their business. Then this study also shows that only 7% of the research sample SMEs present financial statements, with the aim of taxation, profit sharing, and as a tool in making business decisions. While the rest do not present financial reports on the grounds that they do not have guidelines in preparing financial reports. They perceive that financial reports are not important to present and that means they do not need accounting information that is produced by a financial report. This research contributes to the continuity of the SMEs, with the results of this research being the basis for policies related to SMEs.